RANCANGAN APLIKASI MEDIA PEMBELAJARAN PENGENALAN NEGARA G20 BERBASIS 3D MENGGUNAKAN METODE AUGMENTED REALITY - Berry Ikhsan; Ari Usman; Sarudin Sarudin (Jurnal Ilmu Komputer dan Sistem Informasi, 2026)
Global education today increasingly emphasizes the importance of introducing students to cultural, economic, and political diversity around the world. In this context, the introduction of G20 member countries becomes relevant due to their roles in the global economy and international policies, which are also rarely addressed in school lessons about the G20 countries. To facilitate an engaging and interactive learning process, we designed a 3D-based educational media application using Augmented Reality (AR) methods and the FAST (Features from Accelerated Segment Test) Corner detection algorithm to define how well images can be detected and tracked using the Vuforia SDK. This application design aims to provide a profound and captivating learning experience for users. With AR technology, users can directly interact with 3D models of G20 member countries, such as learning about iconic buildings, cultural objects, as well as relevant economic and political information. The application also includes interactive features, including knowledge quizzes and educational games to enhance user engagement. The application development method involves designing an intuitive user interface, developing accurate 3D models, and integrating responsive AR technology. Additionally, the learning content is comprehensively structured, considering various important aspects of each G20 member country. Thus, this application can be an effective tool to enhance users' understanding of global diversity and motivate them to learn more about the roles and contributions of G20 member countries in the modern world context.